Performance of Hybrid Biofilter Based on Rice Husks/Sawdust Treating Grey Wastewater - Villamar-Ayala, C; Costa-Da Conceiacao, K (IWA Publishing, 2023)
An innovative nature-based technology for wastewater treatment is the hybrid biofiltration, which combines complex symbiotic relationships between plants, earthworms and microorganisms with adequate support components. This latter could be optimized using organic supports. The aim of this research was to evaluate the performance of hybrid biofilters based on rice husks/sawdust treating grey wastewater from mining camps. Four biofilters using an active layer (rice husks/sawdust: 50/50%, v/v) at 60(B60) and 45(B45) cm height and operating for 64 days at a hydraulic loading rate between 1 and 5 m3/m2d were monitored. Eisenia foetida Savigny and Cyperus papyrus L. were used as a biotic component. COD, N-NH4þ, NO3-, NO2-, PO43- and fecal coliforms were weekly monitored. Results showed that the most efficient HB was using 60 cm as an active layer and operating at 3 m3/m2d, which reported average removal efficiencies for COD, NH4+, NO3-, PO43- and fecal coliforms up to 85, 89, 47, 49 and 99.9%, respectively. Organic support improved the rate growth for Cyperus papirus L. and E. foetida Savigny up to 50%. Hybrid biofiltration using organic residues is low-cost, providing all-encompassing operational and performance features, improving the wastewater reclamation opportunities. © 2023 The Authors.